Download presentation
Presentation is loading. Please wait.
Published byLynn Wells Modified over 9 years ago
1
CS621: Introduction to Artificial Intelligence Pushpak Bhattacharyya CSE Dept., IIT Bombay Lecture–4: Fuzzy Inferencing 29 th July 2010
2
Meaning of fuzzy subset Suppose, following classical set theory we say if Consider the n-hyperspace representation of A and B (1,1) (1,0)(0,0) (0,1) x1x1 x2x2 A. B 1.B 2.B 3 Region where
3
This effectively means CRISPLY P(A) = Power set of A Eg: Suppose A = {0,1,0,1,0,1,…………….,0,1} – 10 4 elements B = {0,0,0,1,0,1,……………….,0,1} – 10 4 elements Isn’t with a degree? (only differs in the 2 nd element)
4
Subset operator is the “odd man” out AUB, A ∩ B, A c are all “Set Constructors” while A B is a Boolean Expression or predicate. According to classical logic In Crisp Set theory A B is defined as x x A x B So, in fuzzy set theory A B can be defined as x µ A (x) µ B (x)
5
Zadeh’s definition of subsethood goes against the grain of fuzziness theory Another way of defining A B is as follows: x µ A (x) µ B (x) But, these two definitions imply that µ P(B) (A)=1 where P(B) is the power set of B Thus, these two definitions violate the fuzzy principle that every belongingness except Universe is fuzzy
6
Fuzzy definition of subset Measured in terms of “fit violation”, i.e. violating the condition Degree of subset hood S(A,B)= 1- degree of superset = m(B) = cardinality of B =
7
We can show that Exercise 1: Show the relationship between entropy and subset hood Exercise 2: Prove that Subset hood of B in A
8
Fuzzy sets to fuzzy logic Forms the foundation of fuzzy rule based system or fuzzy expert system Expert System Rules are of the form If then A i Where C i s are conditions Eg: C 1 =Colour of the eye yellow C 2 = has fever C 3 =high bilurubin A = hepatitis
9
In fuzzy logic we have fuzzy predicates Classical logic P(x 1,x 2,x 3 …..x n ) = 0/1 Fuzzy Logic P(x 1,x 2,x 3 …..x n ) = [0,1] Fuzzy OR Fuzzy AND Fuzzy NOT
10
Fuzzy Implication Many theories have been advanced and many expressions exist The most used is Lukasiewitz formula t(P) = truth value of a proposition/predicate. In fuzzy logic t(P) = [0,1] t( ) = min[1,1 -t(P)+t(Q)] Lukasiewitz definition of implication
11
Linguistic Variables Fuzzy sets are named by Linguistic Variables (typically adjectives). Underlying the LV is a numerical quantity E.g. For ‘tall’ (LV), ‘height’ is numerical quantity. Profile of a LV is the plot shown in the figure shown alongside. μ tall (h) 1 2 3 4 5 60 height h 1 0.4 4.5
12
Example Profiles μ rich (w) wealth w μ poor (w) wealth w
13
Example Profiles μ A (x) x x Profile representing moderate (e.g. moderately rich) Profile representing extreme
14
Concept of Hedge Hedge is an intensifier Example: LV = tall, LV 1 = very tall, LV 2 = somewhat tall ‘very’ operation: μ very tall (x) = μ 2 tall (x) ‘somewhat’ operation: μ somewhat tall (x) = √(μ tall (x)) 1 0 h μ tall (h) somewhat tall tall very tall
15
Fuzzy Inferencing Two methods of inferencing in classical logic Modus Ponens Given p and p q, infer q Modus Tolens Given ~q and p q, infer ~p How is fuzzy inferencing done?
16
A look at reasoning Deduction: p, p q|- q Induction: p 1, p 2, p 3, …|- for_all p Abduction: q, p q|- p Default reasoning: Non-monotonic reasoning: Negation by failure If something cannot be proven, its negation is asserted to be true E.g., in Prolog
17
Fuzzy Modus Ponens in terms of truth values Given t(p)=1 and t(p q)=1, infer t(q)=1 In fuzzy logic, given t(p)>=a, 0<=a<=1 and t(p >q)=c, 0<=c<=1 What is t(q) How much of truth is transferred over the channel pq
18
Lukasiewitz formula for Fuzzy Implication t(P) = truth value of a proposition/predicate. In fuzzy logic t(P) = [0,1] t( ) = min[1,1 -t(P)+t(Q)] Lukasiewitz definition of implication
19
Use Lukasiewitz definition t(p q) = min[1,1 -t(p)+t(q)] We have t(p->q)=c, i.e., min[1,1 -t(p)+t(q)]=c Case 1: c=1 gives 1 -t(p)+t(q)>=1, i.e., t(q)>=a Otherwise, 1 -t(p)+t(q)=c, i.e., t(q)>=c+a-1 Combining, t(q)=max(0,a+c-1) This is the amount of truth transferred over the channel p q
20
Two equations consistent These two equations are consistent with each other
21
Proof Let us consider two crisp sets A and B 1 U A B 2 U B A 3 U A B 4 U A B
22
Proof (contd…) Case I: So,
23
Proof (contd…) Thus, in case I these two equations are consistent with each other Prove them for other three cases
Similar presentations
© 2025 SlidePlayer.com. Inc.
All rights reserved.